Quantitative risk assessment of fire accidents of large-scale oil tanks triggered by lightning. (May 2016) - Wu, Dongyin; Chen, Zhen
Abstract: Severe fire accidents may be triggered by lightning strikes in large-scale oil tank areas. A methodology was proposed to quantitatively assess the fire risk. Based on previous relevant fire cases, three categories of fire accident scenarios are summarized: (A) fire accidents at the rim seal, (B) fire accidents above the floating roof and (C) fire accidents by perforation of the float pan. A generic event tree was built to present the process of fire development of oil tanks with the protection of a fire extinguishing system and a fire brigade. The probability models were proposed to calculate the probabilities of lightning strike, tank wall and floating roof damage/perforation, failure of the fire protection system and timely response of fire brigade. The application of the methodology to a case study provided the probabilities of different forms of accidents for three categories. According to the results of the case study, the probabilities of rim seal fire, local pool fire and full surface fire of large-scale oil tanks are 1.10 × 10 − 2, 10 − 8 –10 − 6 and 2.17 × 10 − 9, respectively, for Categories A and C, and the probabilities of rim seal fire, local pool fire and full surface fire of large-scale oil tanks are 4.99 × 10 − 2, 10 − 8 –10 − 5 and 9.85 × 10 − 8, respectively, for Category B. The fire risk by lightning for Category B is relatively higher, which could be reduced by improving the design of the float pan and enhancing the reliability of the components. Compared with the hazard of local pool fire and full surface fire, the risk of rim seal fire is unacceptable; in this case, an inert gas protection system can be introduced to reduce the risk. Highlights: We construct the detailed fire accident scenarios with various factors. We build probability models to quantitatively analyze the effect of different factors. The failure probabilities were calculated based on the ETA and FTA method.